Application of Biosheets as Right Ventricular Outflow Tract Repair Materials in a Rat Model - Mizuno, Takeshi; Iwai, Ryosuke; Moriwaki, Takeshi; Nakayama, Yasuhide (Frontiers in Veterinary Science, 2022)
Purposes: We report the experimental use of completely autologous biomaterials (Biosheets) made by “in-body tissue architecture” that could resolve problems in artificial materials and autologous pericardium. Here, Biosheets were implanted into full-thickness right ventricular outflow tract defects in a rat model. Their feasibility as a reparative material for cardiac defects was evaluated. Methods: As the evaluation of mechanical properties of the biosheets, the elastic moduli of the biosheets and RVOT-free walls of rats were examined using a tensile tester. Biosheets and expanded polytetrafluoroethylene sheet were used to repair transmural defects surgically created in the right ventricular outflow tracts of adult rat hearts (n = 9, each patch group). At 4 and 12 weeks after the operation, the hearts were resected and histologically examined. Results: The strength and elastic moduli of the biosheets were 421.3 ± 140.7 g and 2919 ± 728.9 kPa, respectively, which were significantly higher than those of the native RVOT-free walls (93.5 ± 26.2 g and 778.6 ± 137.7 kPa, respectively; P < 0.005 and P < 0.001, respectively). All patches were successfully implanted into the right ventricular outflow tract-free wall of rats. Dense fibrous adhesions to the sternum on the epicardial surface were also observed in 7 of 9 rats with ePTFE grafts, whereas 2 of 9 rats with biosheets. Histologically, the vascular-constructing cells were infiltrated into Biosheets. The luminal surfaces were completely endothelialized in all groups at each time point. There was also no accumulation of inflammatory cells. Conclusions: Biosheets can be formed easily and have sufficient strength and good biocompatibility as a patch for right ventricular outflow tract repair in rats. Therefore, Biosheet may be a suitable material for reconstructive surgery of the right ventricular outflow tract.